Militerisme dan Demokrasi: Evaluasi Hak Politik TNI-Polri di Indonesia Pasca-Reformasi - A. Razaq, Moh. Khalilullah (WELFARE STATE Jurnal Hukum, 2024)
The position of the military in a democratic country is by placingcivilians in the highest power, civilian supremacy over the militaryin history began when the guided democratic government systemwas implemented under President Soekarno. During this period,the military has the same rights as civil society, namely the right tovote and the right to be elected. During the New Ordergovernment, the military did not have political rights, however itsexistence and position became stronger, due to the development ofthe middle way concept initiated by Nasution which became thedoctrine of the Dwifunction ABRI concept. After the 1998 reform,the political system in Indonesia underwent changes, namely theseparation of the positions of the TNI and Polri. This fundamentalchange was marked by the issuance of MPR Decree NumberVI/2000 concerning the Separation of the TNI and Polri and MPRDecree Number VII/2000 concerning the Role of the TNI and Polri.Law Number 34 of 2004 concerning the Indonesian National Armyand Law Number 2 of 2002 concerning the Police of the Republic ofIndonesia. This research uses a normative legal research methodusing a statutory approach, which relies on research to beresearched from a positive legal perspective, and a historicalapproach. This research concludes that the TNI-Polri's politicalrights are prohibited from exercising their political rights and arestill relevant to maintain. And delaying the restoration of politicalrights for the TNI-Polri.